FIM postgraduates Colloquium - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
FIM postgraduate colloquium takes place biannually. For this year, the session was held on 16th June 2016 at the newly renovated lecture room BK01 @ Orange.